Nurses’ high valuation of palliative care versus patient and family misconceptions: A mixed-approach study of Advanced Care Planning implementation in China - Chenyan Liang; Suzhen Lv; Jia Song; Leiwen Tang (PLoS ONE, 2025)
Objective To assess the implementation and barriers of Advance Care Planning (ACP) from the perspectives of nurses, patients, and family members in a Chinese healthcare setting, providing evidence for targeted interventions to enhance ACP awareness. Methods A mixed-methods design combined a cross-sectional survey and qualitative interviews. Questionnaires measured ACP-related knowledge, attitudes, practices (KAP), and perceived barriers among 843 nurses, 384 patients, and 857 family members. Based on responses, 15 patients and 20 family members with negative views on ACP were invited for semi-structured interviews and focus groups. Findings Nurses rated ACP as highly important and reported effective palliative care practices, while patients and families showed substantial cognitive gaps. Over 90% of patients valued ACP, but only ~30% believed it was well implemented; many families associated it with treatment abandonment. Multivariable analysis identified hospital type, clinical experience, and information sources as KAP predictors. Qualitative results linked misconceptions to poor communication and insufficient public education. Conclusion Nurses endorse ACP, but patients and families often misinterpret it as giving up treatment. Improved communication and tailored education are critical to increasing ACP acceptance in China.